Upaya Peningkatan Pengetahuan Ibu Hamil Tentang Gizi Seimbang dan Pentingnya Tablet FE - Chairunnisa Minarni Alamsyah; Reni Nofita; Hanny Desmiati; Nuntarsih Nuntarsih; Dorsinta Siallagan (Universitas Teuku Umar, 2024)
Because the condition of the fetus in the womb largely determines the growth and development of a child, the gestation period determines the quality of human resources and the future. During pregnancy, nutrition and diet are two factors that affect the mother's health. Anemia is a high-risk factor that can cause complications for the mother and fetus. Fe tablets containing iron and folic acid can prevent anemia. Furthermore, another aspect that must be considered by pregnant women is adequate nutritional intake during pregnancy. The aim of this PKM is to prevent anemia with a preventive approach so that it can change adherence to drinking FE tablets and maintain food intake through counseling to increase pregnant women's knowledge about balanced nutrition and the importance of FE tablets. As a result of this community service, the number of pregnant women who scored >80 increased. During the pretest, 44% of pregnant women scored >80, and this number increased to 67% during the posttest. We conducted the pretest-posttest difference test in one group and obtained a significance value of 0.001, indicating a difference in the knowledge of pregnant women before and after counseling.